Implementasi Tax Planning Melalui Instrument Zakat Guna Efisiensi Beban PPH Badan Pada CV. Garmindo Mitra Sejahtera - Fithri, Nadiah Khalishah; Furqon, Imahda Khoiri (Institut Agama Islam Negeri (IAIN) Curup, 2024)
This research aims to find out how the implementation of tax planning through zakat instrument in saving tax expenditure. This research is descriptive research with a quantitative approach with the aim of analyzing, explaining, and concluding the analysis of the implementation of tax planning using the zakat instrument. Data collection techniques in this research are documentation and interviews. This research uses primary data obtained directly from the field. Primary data obtained for research is the income statement of CV. Garmindo Mitra Sejahtera in 2022. From the results of this research analysis, it is concluded that with the implementation of zakat paid to BAZNAS or LAZ or other institutions that have been established and authorized by the government can be used as a deduction for taxable income so as to minimize the Company's payable income tax burden. CV. Garmindo Mitra Sejahtera before the implementation of zakat, the amount of income tax payable amounted to Rp. 2,139,175,727 and profit after applying the implementation of zakat on corporate income tax payable amounted to Rp. 2,085,696,334. Before applying zakat, the payable income tax burden of CV. Garmindo in the 2022 period is Rp. 235,309,329 while after implementing zakat it is Rp. 229,426,596. From the comparison of these calculations, a difference of Rp. 5,882,733 is obtained. This is able to reduce the cost of payable taxes paid.